1988
DOI: 10.1093/oxfordjournals.aje.a114883
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Infection With the Human Herpesviruses in Navajo Children

Abstract: In two random digit dialing surveys conducted among Hispanics using a modified Mitofsky-Waksberg procedure, we found low refusal rates (4.7% and 3.1%), low assumed noncontact rate (14.0% and 18.3%), and high response rates (88.6% and 88.4%) with limited investment in time (1.58 hours and 1.66 hours per completed interview). These results suggest that Hispanics are willing to participate in telephone surveys and that this method may be feasible and useful for research and evaluation purposes. (Am J Public Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As might be expected, the highest prevalence was reported by a study using serological assays [22] and the second highest prevalence (24%) was found using saliva samples [23]. A survey of HIV‐infected children [24] reported a similar high prevalence of 24%, but this paper did not report on the method of determination that the authors employed.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As might be expected, the highest prevalence was reported by a study using serological assays [22] and the second highest prevalence (24%) was found using saliva samples [23]. A survey of HIV‐infected children [24] reported a similar high prevalence of 24%, but this paper did not report on the method of determination that the authors employed.…”
Section: Resultsmentioning
confidence: 75%
“…In the 12 papers reviewed, the reported prevalence was between 0·3% and 73%, and five of these studies surveyed only HIV children, in whom the prevalence ranged between 1·3% and 24%. The methods of determining whether or not an individual suffered from herpes labialis which were reported included, in addition to or instead of a clinical examination, the use of self-report to ascertain a history of the condition [3], serology [22] and saliva sampling [23].…”
Section: Herpes Labialismentioning
confidence: 99%
“…Most primary HSV infections in children are either asymptomatic or so mild that the children or parents do not notice the illness. Some studies have suggested that only 10–12% of children who are infected have signs or symptoms severe enough to be recalled by the child or parent (59), although others have suggested specific clinical manifestation in 25–30% of infected children (60–62). Following an incubation period of 2–20 days, dependent upon the site of infection and the viral strain (57, 58), non‐specific symptoms such as malaise or myalgia can arise, followed, 1–3 days later, by mucocutaneous vesicular eruptions (63).…”
Section: Clinical Associations Of Hsv‐1 Infectionmentioning
confidence: 99%
“…[3,4] Only 13 to 30% of children with primary HSV-1 infection will have gingivostomatitis. [3][4][5] The disease is very contagious, especially in a closed community setting such as a daycare centre or orphanage nursery. [6,7] In these settings, HSV is primarily transmitted by contact with infected oral secretions.…”
Section: Epidemiologymentioning
confidence: 99%